Concentration of roselle (Hibiscus sabdariffa L) and sucrose in beverages Effects on physicochemical characteristics and acceptance - Barajas-Ramírez, Jahir Antonio (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2021)
The calyces of roselle (Hibiscus sabdariffa L.) are used to make a refreshing drink with high content of anthocyanins and other phenolic compounds, although the process for obtaining the beverage is not standardized. In this research it was determined physicochemical characteristics, total soluble polyphenols content, antioxidant activity and acceptance for beverages prepared by decoction at four concentrations of calyces in water (1.0, 2.5, 5.0 and 10.0%) and two concentrations of sucrose (11 and 16%). Color parameters in beverages permitted to describe them as red, which turned darker as the content of hibiscus increased. Total soluble polyphenols content and antioxidant activity were directly correlated with content of calyces in beverages and inversely correlated with pH, which means that beverages with higher content of calyces could be perceived as more acidic and more intense in characteristics associated with hibiscus presence, such as acid, astringent and the presence of intense dark red color, although the higher concentration of sucrose might have contributed to mask slightly the sourness and astringency. Acceptance for hibiscus beverages allowed to observe two segments of consumers, high-intensity and low-intensity likers but both confluence in overall liking values for beverages prepared with 2.5% calyces and 16% sucrose